Community concerns and input for open pit closure in a West African urban setting - Varris, PA; Thorpe, MB (Mine Closure 2012: Seventh International Conference on Mine Closure, 2012)
The Plant North deposit abuts the Prestea community on Golden Star’s Prestea Mining Concession, some 18 km south of Bogoso in the Western Region of Ghana. Operated by Golden Star (Bogoso/Prestea) Limited (GSBPL), mining of the Plant North deposit was approved for operation by the Environmental Protection Agency (EPA) in 2002. Although Prestea has been a mining town since the 1890s, previous mining was primarily underground. The Plant North pit development was the first open pit operation so close to the town of Prestea. The Plant North operation was a key source of gold ore for the GSBPL Bogoso processing plant, however given its proximity to the urban population of Prestea, located within 1 km, the operation was carried out with extensive limitations. Subject to close regulatory enforcement, a temporary stop work order and heavily constrained blasting provisions, the operation was completed in late 2006. At closure, the resulting landscape included an ore stockpile area, a partially backfilled open pit, waste dumps and a large section of pit void developed late in the project life. The project had also resulted in the covering of the Railway spring by waste dumping. Of symbolic and socio-economic importance to the community of Prestea, the Railway spring was a natural groundwater spring used for drinking and domestic purposes. The Plant North Pit closure and rehabilitation plan was the first plan completed by GSBPL in consultation with local community for post closure land use. Based on the understanding that the pit would be backfilled, communities were given an opportunity to provide a next land use plan specifically addressing their needs. These had evolved through the operations and no longer reflected the provisional closure and rehabilitation plans that were included in the environmental impact assessment. The closure and rehabilitation for the Plant North pit was delayed while GSBPL assessed its suitability for development of a portal to the adjacent underground resources. This delay resulted in the EPA establishing a permitting moratorium on GSBPL operations. The development of the portal proved not feasible and, with work being carried out on the pit backfilling, the EPA removed the permitting moratorium. With the support from the community, the closure plan was subsequently approved by the EPA and backfilling was started in earnest in 2010. Backfilling of the pit was completed in late 2011, with about 12 Mm3 of waste material being placed in the pit. During the work, the Railway spring was uncovered and rehabilitated, and the waste dump area was cleared back to original ground. Ongoing work with the community is now being carried out to rehabilitate the capped area of the pit. Further community consultation in regards to closure land use is now being carried out to ensure that the stakeholders are aligned on the multi-use plan for the area. This plan includes a bus transport parking and loading area, agroforestry and areas of secondary tropical forest. It is anticipated that the rehabilitation work will contribute to the ongoing development of the town by providing economic stimuli to employment during the rehabilitation process and more significantly, later, through ongoing use of the area by the community members post closure. GSBPL has learnt many lessons in regards to planning and implementation of closure, particularly in regards to communication and management of stakeholder needs and expectations, in the context of a dynamic mining industry.